2010
DOI: 10.1007/s00128-010-9969-0
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in the Hair of the Individuals in Santana-AP-Brazil: Significance of Residence Location

Abstract: The concentration of arsenic in the hair of the individuals living in Santana city was measured. 121 donors in urban and the periphery area were studied. The periphery of the city shows the highest levels of arsenic (5.94 +/- 6.54 mg kg(-1) - mean; 0.27-23.85 mg kg(-1)). 47.83% in the urban area showed arsenic concentrations of less than 1.00 mg kg(-1), while in the periphery only 11.22% had results below this value. The results showing the influence of residence location. The Principal Component Analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…So far, only few environmental studies include a speciation of As (e.g., inorganic trivalent/pentavalent forms), and the present results are not entirely uniform (Sanz et al 2007;de Fátima Pinheiro Pereira et al 2010). Therefore, it ought to be expected that As speciation research will develop rapidly.…”
Section: Focal Areas Of Present Researchmentioning
confidence: 70%
See 1 more Smart Citation
“…So far, only few environmental studies include a speciation of As (e.g., inorganic trivalent/pentavalent forms), and the present results are not entirely uniform (Sanz et al 2007;de Fátima Pinheiro Pereira et al 2010). Therefore, it ought to be expected that As speciation research will develop rapidly.…”
Section: Focal Areas Of Present Researchmentioning
confidence: 70%
“…It has been estimated that some 4.5 million people in Latin America are chronically exposed to high levels of As ([50 lg/L drinking water), with extremes up to 2,000 lg/L (McClintock et al 2011). Such situations are being further investigated (de Fátima Pinheiro Pereira et al 2010). The World Health Organization has recommended a provisional guideline value of 10 lg/L for arsenic in drinking water (WHO 1996).…”
Section: Contemporary Focus On As Exposuresmentioning
confidence: 99%
“…Initially, GSH participates in the reduction of AsV to AsIII, which is pH dependent and is influenced by the presence of other substances that can be reduced or oxidized; subsequently, the AS3MT participates in the transfer of a methyl group of the SAM enzyme to the trivalent inorganic arsenic to generate MMA(V) Ácido monometilarsónico (monomethylarsonic acid), this compound is reduced to MMA(III) Ácido metilarsenioso (monomethylarsonous acid) by the action of a specific reductase and in this reaction participate the AS3MT, the GSH, and the GSSH, between other compounds; MMAIII enters a methylation reaction to generate DMA(V) Ácido dimetilarsínico (dimethylarsinic acid), and finally, DMAV can be reduced to DMA(III) Ácido dimetilarsenioso (dimethylarsinous acid). These reactions are carried out regardless of the route of absorption [13,15].…”
Section: Absorptionmentioning
confidence: 99%
“…It is known that the ability to meet arsenic is saturated when the ingestion exceeds 0.5 mg/d [16]. The main metabolites found in urine after acute or chronic exposure to arsenic are inorganic arsenic, MMA and DMA [8,17], residual As can also be found in keratinized tissues (skin, hair, and nails), where the presence of arsenic in these tissues has a significant association with chronic exposure to metalloid [15]. Although in general, the presence of arsenic in urine is considered an indicator of acute exposure, it has been found that in prolonged exposures arsenic levels in urine are maintained and increase [8].…”
Section: Excretionmentioning
confidence: 99%
“…The environmental condition of exposures to Arsenics has generated the chief avenues of contemporary research. So far, only scarce environmental studies include a speciation of Arsenic (e.g., inorganic trivalent/pentavalent forms), and the existing results are not totally uniform 91,92 . Therefore, it ought to be projected that Arsenic speciation exploration will further develop.…”
Section: Future Research Scopementioning
confidence: 99%